An Interdisciplinary Clinical Approach for Workplace Violence Prevention and Injury Reduction in the General Hospital Setting: S.A.F.E. Response. (July 2019) - Lakatos, Barbara E.; Mitchell, Monique T.; Askari, Reza; Etheredge, Mary Lou; Hopcia, Karen; DeLisle, Leslie; Smith, Christine; Fagan, Maureen; Mulloy, Deborah; Lewis-O'Connor, Annie; Higgins, Margaret; Shellman, Andrea
BACKGROUND: Workplace violence is a major public health concern. According to the U.S. Bureau of Labor Statistics, from 2002 to 2013, incidents of serious workplace violence (those requiring days off) were four times more common in health care than in private industry.AIMS: An interprofessional committee developed, implemented, and evaluated a quality improvement project from 2012 to 2016 to reduce workplace violence and prevent staff injury. The initiative termed S.A.F.E. Response stands for S pot a threat, A ssess the risk, F ormulate a safe response, E valuate the outcome.METHOD: An institutional review board–approved quality improvement survey was implemented and evaluated. The data were analyzed using descriptive statistics. An interprofessional committee developed and implemented a comprehensive program to prevent injury, which included (a) a mandatory eLearning educational training, (b) a S.A.F.E. Response with standardized interventions for the clinical conditions affecting safety, and (c) a clinical debriefing process. A reduction in nursing staff assault incidence rates was identified as a success.RESULTS: Nursing staff injury rates decreased an average of 40%.CONCLUSIONS: A reduction in nursing staff assault incidence rates was notable. Clinicians equipped with knowledge, skills, and resources can identify and defuse unsafe situations to prevent violence. This clinical approach shifts the focus from crisis intervention to crisis prevention, which reduces injury.